Putting digital artifacts to work - Carter, Scott (2020)
ABSTRACT Physical, collocated work environments are rife with artifacts that are ready-to-hand to serve as tools, conversation props, and content that can be remixed and reused. In digital, distributed environments, on the other hand, work artifacts tend to be siloed and difficult to extricate, making it difficult for remote workers to share interests and knowledge. In this work, we describe set of challenges for developers of systems that support digital artifact reuse. We furthermore show how these challenges are embodied in tools we built that help make digital artifacts reusable. Keywords future of work, digital artifacts, distributed work, distributed tools ABOUT THE AUTHOR/S Scott Carter scott@madpickle.net Targhetta Design Scott Carter has worked in industrial research for over a decade building and evaluating mobile and multimedia systems to support remote and collocated workers. He was most recently a Principal Scientist at FX Palo Alto Laboratory, Inc. and holds a PhD in CS (with an HCI focus) from UC Berkeley. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).